Measurements on slope parameter mapping based on dual-energy CT enterography for improving Crohn’s disease diagnosis and inflammatory activity evaluation - Ziying Lin; Min Hong; Hua Zhong; Xiaoli Zheng; Yu Lin; Dan Yang; Sihui Zhong; Xin Yue (Scientific Reports)
Abstract To explore the value of slope parameter images (SPI) derived from the dual-phase dual-energy CT enterography (DE-CTE) in the diagnosis and activity evaluation of Crohn’s disease (CD). A retrospective analysis of 76 patients with CD and 53 controls who underwent dual-phase DE-CTE between January 2019 and March 2022. CD lesions were divided into non-moderate-to-severe activity (n = 108) and moderate-to-severe activity (n = 59). Virtual monoenergetic images of 40-100 keV and SPI for energy spectrum curves between 40 and 100 keV (SPI40–100) were generated. Virtual monoenergetic CT values (HU40–100keV) and the slope between 40 and 100 keV measured on SPI40–100 (SP40–100) on intestinal wall and adjacent mesenteric fat for the dual phases were collected. The performances of quantitative parameters in the diagnosis and activity assessment of CD were evaluated. The dual-phase SP40–100 and HU40–100 in the affected intestinal wall and adjacent mesenteric fat were higher than those in the control group (P < 0.001). For CD diagnosis, the area under the curve (AUC) of the arterial phase (AP) SP40–100 of mesenteric fat was the highest (AUC = 0.969, P < 0.05). The dual-phase SP40–100 and HU40–100keV of the intestinal wall and creeping fat in those with moderate-to-severe activity were significantly higher than those with non-moderate-to-severe activity (P < 0.001). For activity assessment, AP-SP40–100 of creeping fat had the highest AUC among all parameters (AUC = 0.935, P < 0.05). The measurements on SPI40–100 obtained via dual-phase DE-CTE have high value in CD diagnosis and inflammatory activity evaluation, and the AP SP40–100 of mesenteric fat has the highest diagnostic efficacy.